2017
DOI: 10.1073/pnas.1711389114
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from human pancreatic islets suppress human islet amyloid polypeptide amyloid formation

Abstract: Extracellular vesicles (EVs) are small vesicles released by cells to aid cell-cell communication and tissue homeostasis. Human islet amyloid polypeptide (IAPP) is the major component of amyloid deposits found in pancreatic islets of patients with type 2 diabetes (T2D). IAPP is secreted in conjunction with insulin from pancreatic β cells to regulate glucose metabolism. Here, using a combination of analytical and biophysical methods in vitro, we tested whether EVs isolated from pancreatic islets of healthy patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…PS on these extracellular vesicles interacts with receptors for PS on the surface of various cells including phagocytes, endothelial cells, dendritic cells, and epithelial cells, thereby inducing cellular uptake of the extracellular vesicles 72 , 73 . Importantly, extracellular vesicles such as exosomes reportedly affect the formation of amyloid fibrils by some amyloidogenic proteins such as α-synuclein 74 and IAPP 75 . These lines of evidence together with our findings suggest that extracellular vesicles secreted from a certain type of cells can contribute to or regulate the pathology of amyloidoses.…”
Section: Discussionmentioning
confidence: 99%
“…PS on these extracellular vesicles interacts with receptors for PS on the surface of various cells including phagocytes, endothelial cells, dendritic cells, and epithelial cells, thereby inducing cellular uptake of the extracellular vesicles 72 , 73 . Importantly, extracellular vesicles such as exosomes reportedly affect the formation of amyloid fibrils by some amyloidogenic proteins such as α-synuclein 74 and IAPP 75 . These lines of evidence together with our findings suggest that extracellular vesicles secreted from a certain type of cells can contribute to or regulate the pathology of amyloidoses.…”
Section: Discussionmentioning
confidence: 99%
“…In steady-state conditions it regulates food intake, insulin secretion, and glucose metabolism ( 94 ). Ribeiro et al have noted that pancreatic extracellular vesicles (EVs) from healthy individuals, but not from T2DM patients, directly bind to IAPPs and prevent amyloid formation within the pancreatic islets ( 95 ). The authors showed that the altered protein-lipid composition of the EVs is the main reason for this discrepancy ( 95 ).…”
Section: Effects Of T2dm On the Digestive Systemmentioning
confidence: 99%
“…A group investigating treatments for diabetes focused on pancreatic amyloid deposits in T2D, which have been shown to be a contributor to the disease. Researchers found that secreted exosomes from healthy, but not from T2D patients could slow amyloid formation in in vitro models of T2D . The therapeutic potential of MSC‐derived exosomes was investigated in animal models of diabetes.…”
Section: Role Of Exosomesmentioning
confidence: 99%